State arts policy : trends and future prospects - Lowell, Julia, 1961- (Rand Corporation monograph series., 2008)
State arts agencies -- key players within the U.S. system of public support for the arts -- face growing economic, political, and demographic challenges to the roles and missions they adopted when founded in the mid-1960s. This report, the fourth and final in a multiyear study, looks at state arts agencies' efforts to rethink their roles and missions, reflecting on what the changes may mean for the direction of state arts policy. Drawing on readings, discussions, and analyses conducted for the study, the author concludes that if current trends and strategies continue, future state arts policy is likely to focus more on developing the creative economy, improving arts education, and encouraging a broader spectrum of state residents to participate in the arts. To achieve these goals, state arts agencies will likely become more involved in policy advocacy, coalition building, convening, and gathering and disseminating information than in grantmaking. The transition to this future poses some risks for the agencies and for the arts community, but it also offers the opportunity to more effectively promote the conditions in which the arts can thrive.